How not to become a crypto-jacking statistic. Issue 4 (April 2019) - Norman, James
Abstract : Successful businesses are constantly reinventing themselves to stay aligned with customer interests and buying habits, and successful cyber criminals do exactly the same. When one method ceases to be as effective as it once was, cyber criminals seek out a new source of revenue. For example, ransomware has been a known danger for years, but in the first half of 2018, a new vector of attack known as crypto-jacking replaced ransomware as the most popular digital threat.